PENGARUH TINGKAT UPAH, KESEJAHTERAAN DAN LOYALITAS TERHADAP KINERJA KARYAWAN PADA PT. SAPADIA BOOMBARA WATERPARK RANTAUPRAPAT - Broto, Bayu Eko (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2020)
The purpose of this study was to determine the effect of wage levels, welfare, and employee loyalty on the performance of employees of PT. Sapadia Boombara Waterpark Rantauprapat either partially or simultaneously. The number of samples taken in this study were 35 employees of PT. Sapadia Boombara Waterpark Rantauprapat. This study uses a questionnaire which is used as a tool to collect data, and to fill out the questionnaire the respondents will fill in using a Likert scale 1-5. The results of filling out the questionnaire will be tested using SPSS 20 software. Tests carried out in this study are to use validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study found that the level of wages partially has a positive effect on employee performance at PT. Sapadia Boombara Waterpark Rantauprapat. Training partially has a positive and significant effect on welfare at PT. Sapadia Boombara Waterpark Rantauprapat. Loyalty partially has a positive and significant effect on employee performance at PT. Sapadia Boombara Waterpark Rantauprapat. The level of Wages, Welfare and Loyalty simultaneously (together) have a significant effect on Employee Performance at Sapadia Boombara Waterpark Rantauprapat.